Academic Performance Among Children With Sickle Cell Disease in Low‐ and Middle‐Income Countries: A Systematic Review - Shubaya K. Naggayi; Paul Bangirana; Simple Ouma; Mary Nyakato; Alison A. Kinengyere; Dickens Akena; Nancy S. Green; Richard Idro (Health Science Reports, 2026)
ABSTRACT Background and Aim Children with sickle cell disease (SCD) in low‐ and middle‐income countries (LMICs) face significant disease‐related challenges and socioeconomic status (SES) disparities that may negatively impact their academic performance. This systematic review synthesized existing evidence on academic performance among children with SCD in LMICs. Methods We conducted a comprehensive search in PubMed, PsycINFO, ERIC, and SCOPUS (January 1980–July 2026) using controlled vocabulary and free‐text terms related to SCD and academic performance. We included cross‐sectional studies and one prospective study involving children under 18 years with SCD in LMICs. Eligible studies reported on academic performance outcomes across two measures: academic achievement and grade attainment. Comparator groups were children without SCD. Studies outside LMICs and in languages other than English were excluded. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross‐Sectional Studies and Newcastle–Ottawa Scale (NOS). The review was conducted and reported following the PRISMA 2020 guidelines. Owing to the heterogeneity of assessment measures, a meta‐analysis could not be undertaken. Findings were synthesized narratively using the Synthesis Without Meta‐analysis approach. Results Of 165 records screened, 11 studies met the inclusion criteria, comprising 1630 participants. Seven of the 11 studies meeting the inclusion criteria had reported poorer academic performance among children with SCD compared to healthy peers, siblings, relatives, or neighborhood controls. Findings varied according to the academic performance measures and analytic approaches employed across studies. Several studies reported poorer academic performance and higher rates of grade repetition among children with SCD compared to controls. Older age and school absenteeism were among the factors most commonly associated with poorer academic outcomes. Conclusion Evidence suggests that children with SCD in LMICs may be at increased risk of academic difficulties. Particular attention may be needed for older children with SCD and those with frequent school absenteeism. Systematic Review Registration PROSPERO CRD42022200619.